If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-5-2t=9+5t
We move all terms to the left:
-5-2t-(9+5t)=0
We add all the numbers together, and all the variables
-2t-(5t+9)-5=0
We get rid of parentheses
-2t-5t-9-5=0
We add all the numbers together, and all the variables
-7t-14=0
We move all terms containing t to the left, all other terms to the right
-7t=14
t=14/-7
t=-2
| 3x-7(2x-20)=85 | | -3g+12=48 | | 22-y=185 | | m-18.95=16.7 | | 17+v=-11v-19 | | 3(2m+9)=6m+27 | | u-27=9 | | 8c=65 | | y+40=100 | | k-4.3=6.9 | | 2(4t)=16t | | 3.1p-7=2.1p-7 | | 14y-20y=36 | | -6j+5=-5-4j | | 10(g+3.50=75 | | 7x-9+3x+15=180 | | Y=4(x+5)^3-1 | | -9t=-17-10t | | r/6=23 | | -1-2x=-23 | | 8x-5=27+6x | | -88=-4(-4r+6) | | 4x(5+3)=(4x)+(4x) | | p-12.08=7.45 | | 920x=8,000 | | -8m=-104 | | 180=70+65x+53 | | 3u-4=-2 | | 12/40=3/x | | m+7=3+m5 | | -7+7z=9+5z-2 | | 4(5+x)=-7(2-2x) |